Cellulosome assembly: paradigms are meant to be broken!. (April 2018) - Bule, Pedro; Pires, Virgínia MR; Fontes, Carlos MGA; Alves, Victor D
Abstract : Cohesin–Dockerin interactions are at the core of cellulosomal assembly and organization. They are highly specific and form stable complexes, allowing cellulosomes to adopt distinct conformations. Each cellulosomal system seems to have a particular organizational strategy that can vary in complexity according to the nature of its Cohesin–Dockerin interactions. Hence, several efforts have been undertaken to reveal the mechanisms that govern the specificity, affinity and flexibility of these protein–protein interactions. Here we review the most recent studies that have focused on the structural aspects of Cohesin–Dockerin recognition. They reveal an ever-increasing number of subtle intricacies suggesting that cellulosome assembly is more complex than was initially thought.